SARS-CoV-2 Vaccine Hesitancy in a Sample of US Adults: Role of Perceived Satisfaction With Health, Access to Healthcare, and Attention to COVID-19 News - Bass, Sarah Bauerle; Wilson-Genderson, Maureen; Garcia, Dina T.; Akinkugbe, Aderonke A.; Mosavel, Maghboeba (Frontiers in Public Health, 2021)
Understanding which communities are most likely to be vaccine hesitant is necessary to increase vaccination rates to control the spread of SARS-CoV-2. This cross-sectional survey of adults (n = 501) from three cities in the United States (Miami, FL, New York City, NY, San Francisco, CA) assessed the role of satisfaction with health and healthcare access and consumption of COVID-19 news, previously un-studied variables related to vaccine hesitancy. Multilevel logistic regression tested the relationship between vaccine hesitancy and study variables. Thirteen percent indicated they would not get vaccinated. Black race (OR 2.6; 95% CI: 1.38–5.3), income (OR = 0.64; 95% CI: 0.50–0.83), inattention to COVID-19 news (OR = 1.6; 95% CI: 1.1–2.5), satisfaction with health (OR 0.72; 95% CI: 0.52–0.99), and healthcare access (OR = 1.7; 95% CI: 1.2–2.7) were associated with vaccine hesitancy. Public health officials should consider these variables when designing public health communication about the vaccine to ensure better uptake.